Understanding confidence in the human papillomavirus vaccine in Japan: a web-based survey of mothers, female adolescents, and healthcare professionals - Michiko Shuto; Youngju Kim; Kotoba Okuyama; Kazunobu Ouchi; Hideo Ueichi; Chimeremma Nnadi; Heidi J. Larson; Gonzalo Perez; Shin Sasaki (Taylor & Francis Group, 2021)
Vaccine confidence reflects social, individual, and political factors indicating confidence in vaccines and associated health systems. In Japan, the government ceased proactive recommendation of the human papillomavirus (HPV) vaccine in June 2013, only several months after the recommendation had begun. Seven years later, as of October 2020, the suspension persists and vaccine coverage has precipitously declined, resulting in many young women being continually exposed to the risk of preventable HPV-related diseases. Accordingly, understanding stakeholder opinions on HPV vaccination issues is critical for informing strategies to improve HPV vaccine confidence and acceptance. In October 2019, we performed a nationwide, web-based survey of 1646 mothers of HPV-vaccination-eligible girls, 562 female adolescents aged 15-19 years, and 919 healthcare professionals (HCPs) in Japan. This survey captured key elements of vaccine confidence (i.e., importance, effectiveness, and safety of the HPV vaccine), awareness, and the willingness to receive (in HPV-vaccination-eligible girls) or recommend (in HCPs) the HPV vaccine, and the factors responsible for these decisions. HPV vaccine confidence was generally higher among HCPs than among mothers or female adolescents. Nearly half of all stakeholders were neutral regarding their willingness to receive/recommend the HPV vaccine. The seriousness of cervical cancer and the HPV vaccine's effectiveness or safety were important deciding factors for receiving/recommending the HPV vaccine. Besides these factors, sufficient information and free vaccination were crucial. Our results suggest several factors that could help shape public policy and communication strategies to improve HPV vaccine confidence and acceptance in Japan.